Optimizing inhaled corticosteroid use in patients with chronic obstructive pulmonary disease: assessing blood eosinophils, neutrophil–to–lymphocyte ratio, and mortality outcomes in US adults - Hu, Han-Shuo; Wang, Zhuo; Jian, Ling-Yan; Zhao, Li-Mei; Liu, Xiao-Dong (Frontiers in Immunology, 2023)
Objective: Accurate biomarkers for evaluating mortality rates in patients with chronic obstructive pulmonary disease (COPD) remain scarce. This study aimed to explore the relationships between mortality rates in patients with COPD and blood eosinophil counts, neutrophil counts, and lymphocyte counts, along with the neutrophil–to–lymphocyte ratio (NLR). Additionally, we sought to identify the optimal response values for these biomarkers when utilizing inhaled corticosteroids (ICS). Methods: Utilizing a nationally representative, multistage cross–sectional design and mortality correlation study, we analyzed data from the National Health and Nutrition Examination Survey (1999–2018) involving US adults aged 40 years or older with COPD. The primary endpoint was all–cause mortality, with Kaplan–Meier survival curves and restricted cubic splines applied to illustrate the relationship between leukocyte–based inflammatory markers and mortality. The analysis was conducted in 2023. Results: Our analysis included 1,715 COPD participants, representing 6,976,232 non–institutionalized US residents [weighted mean age (SE), 62.09 (0.28) years; range, 40–85 years]. Among the participants, men constituted 50.8% of the population, and the weighted mean follow–up duration was 84.9 months. In the ICS use group, the weighted proportion of participants over 70 years old was significantly higher compared with the non–ICS use group (31.39% vs 25.52%, p < 0.0001). The adjusted hazard ratios for all–cause mortality related to neutrophil counts, lymphocyte counts, and NLR were 1.10 [95% confidence interval (CI), 1.04–1.16, p < 0.001], 0.83 (95% CI, 0.71–0.98; p = 0.03), and 1.10 (95% CI, 1.05–1.15; p < 0.0001), respectively. Optimal ICS response was linked with higher levels of eosinophil count (≥240 cells/μL), neutrophil count (≥3,800 cells/μL), NLR (≥4.79), and lower levels of lymphocyte count (<2,400 cells/μL). Conclusion: Adjusted baseline neutrophil, lymphocyte counts, and NLR serve as independent risk factors for all–cause mortality in patients with COPD. Further, ICS application appears to mitigate mortality risk, particularly when NLR levels reach 4.79 or higher, underlining the importance of ICS in COPD management.